Relationship between Particle Size Distribution and Pollutant Content during the Transport of Storm Runoff - GAO Aiping; HUANG Tinglin; MA Xu; ZHANG Guorong; FAN Wenwei; QI Yunzhi; ZHANG Bo; DU Juanjuan; CUI Hongjun (Renmin Zhujiang, 2024)
Flood season runoff is an important factor affecting reservoir operation, and timely understanding of the runoff transport and the corresponding water quality responses during flood season can provide suggestions for reservoir operation. In-situ field monitoring is conducted at the Jinpen Reservoir, and water quality is analyzed through photometry and atomic absorption to study the reservoir runoff. It is found that the runoff's transport progress and the location where it enters the reservoir area are mainly influenced by its volume. The inflow on October 3 is three times larger than that on April 4 and 2.6 times larger than that on June 3, while the TP content is five times higher than that on June 3, and the CODMn is 1.8 times and 1.7 times higher than that on these two days, respectively, indicating that the TP and CODMn in the inflow are related to its volume. The inflow on April 4 and June 3 is nearly the same, but the TN and NO3-N on April 4, when the initial runoff happens, are 2.2 times and 1.7 times larger than that on June 3 respectively, indicating that TN and NO3-N are greatly influenced by the initial runoff. On October 3, the runoff contains over 70% of suspended particles larger than 10 μm. The turbidity reduction turned slow when it decreased to 30 NTU after the runoff entered the reservoir. Moreover, the pollutants carried by the particle are inversely proportional to the particle's size, leading to substandard water quality in the reservoir during the flood season. Under the rapid deterioration of reservoir water quality during the flood season, the quality of the water supply can be improved by releasing the high-turbidity water carried by the runoff through the flood discharge tunnel to ensure clean water storage and using elevated water intakes.